Surnames of the ukrainian population as a tool of population and genetic research - L.O. Atramentova; V.V. Shuba; M.Yu. Gorpinchenko (Вісник Харківського Національного Університету Імені В.Н. Каразіна: Серія Біологія)
The article presents the results of population genetic research, Execution with the help of surnames. It is proved that Ukrainian surnames meet the previous requirements for them as a tool of population genetic research: the stench is stably inherited for more than ten generations by patrilineal type; semantics and morphology are the most diverse in the world; unevenly distributed throughout the country, differing in history, demographic processes, anthropological types of population, the distribution of biological markers. According to the correlation coefficients between the weight of the ethnic group in the population and the number of ethnic surnames, a direct connection was found. There is also a direct link between the matrix of genetic distances calculated by blood groups, haplogroups of the Y chromosome and distances by surnames. A rather strong connection of surnames with genetic markers provides a basis for extrapolating the values obtained with the help of surnames to the gene pool of the population. The distribution of the 20 most frequent surnames in different regions is shown. Calculated indicators that reflect the structure of the population and the genetic processes that take place in them: index of isonymy Ir, diversity α, inbreeding Fst, migration ν, order H and redundancy distribution R. These indicators are compared between populations in geographical and hierarchical location. The isonymy index shows a clear gradient that increases in the direction from the southeast to the northwest. Other indicators also change their value quite clearly from the South-East to the North-West directions. At lower levels of the population structure, the differential ability of indicators calculated by surnames increases. At the level of district populations, Identifying the founder's effect is analogous to genetic drift, which is particularly clearly demonstrated by the index of the place Ip. The distribution of population indicators is explained by historical events and demographic processes that have taken place in the history of the country.